2013
DOI: 10.1038/nn.3489
|View full text |Cite
|
Sign up to set email alerts
|

The Parkinson's disease–linked proteins Fbxo7 and Parkin interact to mediate mitophagy

Abstract: Compelling evidence indicates that two autosomal recessive Parkinson’s disease genes, PINK1 (PARK6) and Parkin (PARK2), co-operate to mediate the autophagic clearance of damaged mitochondria (mitophagy). Mutations in the F-box domain containing protein Fbxo7 (PARK15) also cause early onset autosomal recessive Parkinson’s disease by an unknown mechanism. Here we show that Fbxo7 participates in mitochondrial maintenance through direct interaction with PINK1 and Parkin and plays a role in Parkin-mediated mitophag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
323
0
7

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 295 publications
(341 citation statements)
references
References 46 publications
11
323
0
7
Order By: Relevance
“…Alternatively, cells were fixed for immunocytochemistry in a 4% PFA PBS solution for 10 min at room temperature (16). Antibodies used were: anti-Pink1 (Novus Biologicals BC100 -494 1:1000), mouse anti-FLAG (Sigma F3165, 1:2,000), rabbit anti-FLAG (Sigma F7425, 1:5,000), anti-complex V␤ subunit (Abcam ab14730, 1:500), anti-Mfn1 (Abcam ab57602, 1:1,000 for WB), antiComplex V␣ (1:5,000, Abcam ab14730), HtrA2 (Cell Signaling, 1:4000) anti-LC3 (Novus NB100 -2220).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternatively, cells were fixed for immunocytochemistry in a 4% PFA PBS solution for 10 min at room temperature (16). Antibodies used were: anti-Pink1 (Novus Biologicals BC100 -494 1:1000), mouse anti-FLAG (Sigma F3165, 1:2,000), rabbit anti-FLAG (Sigma F7425, 1:5,000), anti-complex V␤ subunit (Abcam ab14730, 1:500), anti-Mfn1 (Abcam ab57602, 1:1,000 for WB), antiComplex V␣ (1:5,000, Abcam ab14730), HtrA2 (Cell Signaling, 1:4000) anti-LC3 (Novus NB100 -2220).…”
Section: Methodsmentioning
confidence: 99%
“…Here we show that FCCP changes intracellular pH, which induces mitophagy. Importantly, other physiological processes that induce mitophagy, such as hypoxia and starvation, also induce mild acidification of the cytosol (12)(13)(14)(15)(16). Changes in intracellular pH activates autophagy (17,18).…”
mentioning
confidence: 99%
“…Depletion of DJ-1, another Parkinson's-disease-associated gene, disrupts both mitochondrial dynamics and morphology (Hao et al, 2010;Irrcher et al, 2010;Thomas et al, 2011). In addition, two other Parkinson's-diseaseassociated proteins, F-box domain-containing protein (Fbxo7; also known as PARK15) and sterol regulatory element binding transcription factor (SREBF1) are also implicated in mitophagy (Burchell et al, 2013;Ivatt et al, 2014).…”
Section: Dynamics Of Mitochondrial Degradation In Neurodegenerative Dmentioning
confidence: 99%
“…Defects in mitochondrial quality control have been implicated in neurodegenerative conditions such as PD largely based on genetic mutations associated with familial, early onset forms of the disease. 2,3 In particular, there have been multiple associations between disease and mutations that disrupt a process called mitophagy, or the ability of damaged mitochondria to self-destruct. Mitophagy is a cellular quality control mechanism that selectively eliminates the damaged organelle and thereby protects the cell from death.…”
Section: All In the Familymentioning
confidence: 99%
“…a team of British researchers led in part by helene Plun-Favreau, a senior lecturer in the Department of molecular neuroscience at the UCL Institute of Neurology, recently reported that, similar to ParK2, FBXO7 plays a role in mitophagy downstream of PinK1. 3 "We are planning to do some compound screening in the near future to try and correct or improve mitophagy. One possibility would be to try to improve ParK2 and/or FBXO7 recruitment to damaged mitochondria," she said.…”
Section: All In the Familymentioning
confidence: 99%